Seminar on protocol & effective master of ceremonies - Achan, Pauline (Universiti Teknologi MARA, Sarawak, 2009)
The seminar was attended by 100 students from the various faculties in UiTM Sarawak. The topics chosen are very relevant as students need to acquire other knowledge and skills apart from what is taught in the classrooms. Administrative office personnel are often required to organize events for their organization, as such it is pertinent that the would-be graduates from the Faculty of Office Management & Technology be aware of the correct protocol since any event will not be successfully organized if the correct protocol is not adhered to, whilst at the same time painting a negative picture of the organizers. Equally important is the role of the Master of Ceremonies as he or she plays a very critical role in ensuring the event runs smoothly, lively or dull.